Learning or lock-in: Optimal technology policies to support mitigation - Matthias Kalkuhl; Ottmar Edenhofer; Kai Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
We investigate conditions that aggravate market failures in energy innovations, and suggest optimal policy instruments to address them. Using an intertemporal general equilibrium model we show that 'small' market imperfections may trigger a several decades lasting dominance of an incumbent energy technology over a dynamically more efficient competitor, given that the technologies are very good substitutes. Such a 'lock-in' into an inferior technology causes significantly higher welfare losses than market failure alone, notably under ambitious mitigation targets. More than other innovative industries, energy markets are prone to these lock-ins because electricity from different technologies is an almost perfect substitute. To guide government intervention, we compare welfare-maximizing technology policies in addition to carbon pricing with regard to their efficiency, effectivity, and robustness. Technology quotas and feed-in-tariffs turn out to be only insignificantly less efficient than first-best subsidies and seem to be more robust against small perturbations.
Keywords: O38; Q40; Q54; Q55; 330; renewable energy subsidy; renewable portfolio standard; feed-in-tariffs; carbon pricing; Förderung regenerativer Energien; Forschungs- und Technologiepolitik; Energietechnik; Klimaschutz; Technologiewahl; Ökosteuer; Energiesubstitution; Subvention; Policy-Mix; Theorie